Poetic Didactic Texts in Qur’anic Readings (Qirāʾāt): Their Origins and Types (The International Journal of Educational Sciences and Arts, 2025)
This study examines didactic poems (manẓūmāt) in the science of Qur’anic readings (ʿilm al-qirāʾāt) in terms of their origins and main types, viewing them as an educational tool that has contributed to systematising qirāʾāt issues and facilitating their memorisation and recall. This came after an earlier phase in which students relied primarily on concise prose manuals such as al-Taysīr, al-ʿUnwān and al-Irshād. The study originates from the problem of the relative scarcity of works that gather qirāʾāt manẓūmāt and present them to the student in an organised format that makes them easier to use.The research adopts a descriptive–analytical method, based on collecting material related to these didactic poems, classifying it according to subject, and restricting the discussion to a concise presentation appropriate to the nature of the study. The first section surveys the emergence of didactic verse in ancient civilisations, then follows the development of didactic poetry in Islamic civilisation, before outlining the beginnings of poetic composition in qirāʾāt and establishing that the first to versify the seven readings was al-Ḥusayn b. ʿAlī b. Thābit al-ḍarīr al-Baghdādī in his poem al-Murshid, and that the earliest poem to reach us is al-Ḥuṣrī’s qasīda on the reading of Imām Nāfiʿ.The study then presents the main types of manẓūmāt in ʿilm al-qirāʾāt, including: poems on the transmission (riwāya) of the seven readings, the ten, the three completing the ten, and those beyond the ten; poems devoted to a single reading, narration, or route (ṭarīq); poems on major and minor principles (uṣūl); poems on the taḥrīrāt of al-Shāṭibiyya and al-Ṭayyiba; poems attributing (ʿazw) the various reading options; poems on additional readings (zawāʾid); and riddle-poems in qirāʾāt. The findings highlight the breadth of this legacy and the distinctive scholarly schools that emerged in it, such as the Wāsiṭ school in Iraq and the Maghribī school in the reading of Nāfiʿ and its manẓūmāt, with continued composition in this field into the later Islamic periods.The study concludes by recommending an extensive project to identify and catalogue qirāʾāt manẓūmāt, distinguishing what is lost, what survives in manuscript form, and what has been edited and printed; and to devote further descriptive–analytical work to editing the extant manuscripts and tracing lost poems in manuscript collections, so as to bring out their value in serving the science of Qur’anic readings.
Keywords: Didactic Poems (Manẓūmāt); Didactic Verse (Naẓm); Poem (Manẓūma); Qur’anic Readings (Qirāʾāt)